Atrial Fibrillation in Patients with Embolic Stroke of Undetermined Source during 3 Years of Prolonged Monitoring with an Implantable Loop Recorder - Kitsiou, Alkisti; Rogalewski, Andreas; Kalyani, Malik; Deelawar, Sameera; Tribunyan, Sona; Greeve, Isabell; Minnerup, Jens; Israel, Carsten; Schäbitz, Wolf-Rüdiger (Thrombosis and Haemostasis, 2021)
Background Undocumented atrial fibrillation (AF) is suspected as a main stroke cause in patients with embolic stroke of undetermined source (ESUS), but its prevalence is largely unknown. This prospective study therefore aimed at delineating the prevalence of AF in patients with ESUS using continuous cardiac monitoring by implantable loop recorder (ILR) with daily remote interrogation over a period of 3 years and its clinical consequences, including recurrent stroke.Methods In consecutive patients with an ESUS diagnosis after complete work-up, an ILR was implanted and followed by daily remote monitoring until AF was detected or a follow-up of at least 3 years was completed. Additionally, the ILR was interrogated in-hospital in 6-month intervals.Results A total of 123 patients (74 male, mean age 65 ± 9 years) were enrolled and completed the 3 years study period. AF was detected in 51 patients (41.4%). In 43 of the 51 AF positive patients (84%) oral anticoagulation was established. Recurrent strokes occurred in 18 patients (14.6%) of this ESUS population, 9 of these patients being AF positive (17.6% of the AF-positive patients) and 9 being AF negative (12.5% of AF-negative patients). Patients with AF were slightly older than patients without AF (63.1 ± 8.8 vs. 67.5 ± 9.6 years, p = 0.12). Other parameters such as CHA2DS2-VASc score, infarct localization, micro- and macroangiopathy, carotid or aortic plaques, or stroke recurrence were not significantly different between groups.Conclusion In ESUS patients, early implantation of an ILR with cardiac monitoring and remote transmission over a 3-year period detected AF in 41.4% and resulted in oral anticoagulation in 84% of these patients.
Keywords: atrial fibrillation; embolic stroke of undetermined source; implantable loop-recorder; remote monitoring; stroke